Induction of human autorosette forming cells by phorbol myristate acetate. - Sakano, T (1982)
Human peripheral blood lymphocytes were examined for rosette formation with autologous erythrocytes. When normal human lymphocytes were stimulated with phorbol myristate acetate (PMA) in the presence of autologous serum, the levels of autorosette forming cells (ARFC) were strongly enhanced. Pre-culture was necessary for the generation of ARFC by PMA and the maximal level of ARFC was observed at 72 hr of culture. ARFC appear to belong to a T cell subset and the induction of ARFC by PMA was noted in monocyte depleted lymphocyte fractions, indicating monocyte independency.